KONSEP DASAR DAN IMPLEMENTASI PEMBELAJARAN KONTEKSTUAL - Hamruni Hamruni (Jurnal Pendidikan Agama Islam, 2015)
Learning strategies is one aspect to be prepared by teachers in performing their tasks. Learning strategy outlines a course of action in order to achieve the objectives. By implementing a strategy, teacher can act based on guidelines regarding the various alternatives that may be pursued, so that teaching and learning can take place in a systematic, purposeful, smooth and effective way. One strategy that can be developed by teacher is contextual learning. Contextual learning or also known as CTL (Contextual Teaching and learning) is a process of learning that emphasizes the involvement of students to be able to find the material studied and connect with real-life situations, thus encouraging students to be able to apply it in their lives. This article discusses the concept and implementation of learning contextual where learning is more emphasis on student activity fully, both physically and mentally, the class rather than as a place to obtain information, but rather a place to examine data from their findings in the field, learning is not just memorize, but the process experienced in real life